2018
DOI: 10.1002/dta.2419
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of N,N‐dimethylamphetamine in wastewater – a pyrolysis marker and synthesis impurity of methamphetamine

Abstract: The increased availability of high purity crystalline methamphetamine (MA) in Australia raised concerns because of high dosages and its potential consumption through inhalation. The present work investigates the possibility of using wastewater levels of N,N-dimethylamphetamine (DMA), a pyrolysis by-product, as an indirect indicator of MA smoking. A dedicated liquid chromatography quadrupole-time-of-flight mass spectrometry (LC-QToF-MS) method was set up to detect and quantify DMA in wastewater samples. Wastewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…With regard to cocaine, purity has fluctuated between 6.2% and 98% in Australia, Europe, and United States . For amphetamine and methamphetamine, data collected in the same countries have shown fluctuation from 1% to 44% and 3% to 83%, respectively , while 3,4‐methylenedioxyamphetamine (MDA) and/or 3,4‐methlyenedioxymethamphetamine (MDMA) purity in Europe has ranged from 62% to 79% .…”
mentioning
confidence: 99%
“…With regard to cocaine, purity has fluctuated between 6.2% and 98% in Australia, Europe, and United States . For amphetamine and methamphetamine, data collected in the same countries have shown fluctuation from 1% to 44% and 3% to 83%, respectively , while 3,4‐methylenedioxyamphetamine (MDA) and/or 3,4‐methlyenedioxymethamphetamine (MDMA) purity in Europe has ranged from 62% to 79% .…”
mentioning
confidence: 99%
“…The use of spiked samples to perform method validation is a common standard due to the lack of CRMs for OMPs in water samples. Only one publication mentions the use of an interlaboratory study for the validation of an analytical method (50). Regarding the use of spiked samples, two different groups of studies were identified: those that used an authentic matrix for performing method validation, which obtained 4 points for validation strategy, and those that used ultrapure water, drinking water, or a different water for method validation, which obtained 2 points.…”
Section: Key (Wastewater) or Title-abs-key (Surface And Water) Or Tit...mentioning
confidence: 99%
“…The war against drugs is fierce, and police forces around the world are in great need of drug-detection methods to guide the investigation and conviction of drug dealers. Currently, the detection of drugs in analytical laboratories is mainly based on chromatography, 1–3 mass spectrometry, 4–7 Raman spectrometry, 8–18 and immunoassay. 7,19–24…”
Section: Introductionmentioning
confidence: 99%